2016
DOI: 10.5539/ijef.v8n7p21
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Corporate Liquidity in Real Estate Industry: Evidence from Vietnam

Abstract: This paper investigates the impact of firm size, profitability, cash flows, investment opportunities, leverage and capital expenditure on cash holding level and cash conversion cycle for 54 listed real estate companies in Vietnam stock exchange during 2010-2014. The empirical result highlights two most important variables that affect the cash holdings-profitability and capital expenditure that have strong influence on the corporate liquidity of these real estate companies. The study also indicates that policie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
2
1
3
Order By: Relevance
“…According to the study conducted by Rajkumar (2014), a negative relationship between the financial leverage and the financial performance of the John Keells Holding plc in Sri Lanka was reported. Moreover, there is also research regarding the determinants of corporate liquidity in real estate industry, evidence from Vietnam, which concludes that the corporate liquidity of these real estate companies was affected by cash holding profitability and capital expenditure (Trinh & Mai, 2016). Based on Javed et al (2015), financial leverage was negatively associated with the return on assets and equity empirical evidence from Pakistan, and the firms borrowed less, while market-to-book ratio shows a positive profitable association with firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the study conducted by Rajkumar (2014), a negative relationship between the financial leverage and the financial performance of the John Keells Holding plc in Sri Lanka was reported. Moreover, there is also research regarding the determinants of corporate liquidity in real estate industry, evidence from Vietnam, which concludes that the corporate liquidity of these real estate companies was affected by cash holding profitability and capital expenditure (Trinh & Mai, 2016). Based on Javed et al (2015), financial leverage was negatively associated with the return on assets and equity empirical evidence from Pakistan, and the firms borrowed less, while market-to-book ratio shows a positive profitable association with firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Arfan et al, 2017;Guizani, 2017;Herlambang et al, 2019;Maheshwari and Rao, 2017;Serly and Melendy, 2021;Tayem, 2017) find that high levels of corporate capital expenditure will reduce the amount of cash holding because it is used to finance capital expenditure. (Thu and Khuong, 2018;Trinh and Thuy Mai, 2016) Found contradictory results, namely, the amount of cash holding will increase as the company's capital expenditure increases. Meanwhile, (Amalia et al, 2018;Liadi and Suryanawa, 2018) found that the determination of the amount of cash holding was not influenced by the company's capital expenditures.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Kemudahan perusahaan dalam memperoleh pendanaan dari pihak luar yang digunakan untuk memenuhi kebutuhan atau pembelian aset tetap baru menjadi alasan perusahaan untuk tidak memiliki cash holding dalam jumlah besar. Hasil penelitian ini juga tidak mendukung penelitian yang sebelumnya dilakukan oleh Trinh & Thuy Mai (2016) yang menemukan adanya pengaruh positif capital expenditure terhadap cash holding. Perusahaan dengan tingkat capital expenditure tinggi justru akan menyimpan kas dalam jumlah banyak sebagai bentuk kewaspadaan saat perusahaan dihadapkan pada kejadian tidak terduga.…”
Section: Hasil Penelitianunclassified